ARTYSTA WPISANY W DZIEŁO. MIĘDZY LAS MENINAS DIEGO VELAZQUEZA A NEW NIGHTMARE WESA CRAVENA - Dunin-Wilczyński, Stanisław (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
Diego Velazquez’s painting „Las Meninas” corresponds with Wes Craven’s film „New Nightmare” on thematic and visual levels. They are connected not only by the motif of an author within his work, but also by the means to which this motif is used. On the one hand it might be interpreted as a fairly egotistic act, which intends to underline the value of their work and their artistic mastery. However, at the same time it is a masterful play with the viewer who comes to see their works. Craven’s work takes from the baroque understanding of representing reality, where the aim is to amaze by blur the border between the reality represented on the image and the base reality of the viewer.